Adapting Mindfulness-Based Interventions for Residents of Long-Term Care Facilities - Christian Terry MA (SAGE Publishing, 2021)
Mindfulness-based interventions (MBIs) have received increased clinical attention in recent years. While some MBI research has focused on healthy older adults, research with more emotionally and physically vulnerable populations, such as residents of long-term care facilities (LTCFs), is lacking. The current paper presents quantitative and qualitative results from a pilot study of an individual MBI designed for residents of LTCFs. Participants included 8 residents from two skilled nursing facilities in the southeastern United States. Data were collected between October 2016 through June 2017. A modified MBI is proposed with specific adaptations for LTCF residents. Recommended adaptations for LTCFs include a shift from a group to an individual format, individual weekly instructor–participant meetings, removal of the yoga and full-day silent retreat and shortening the duration of the formal practices. The current study found that these adaptations result in an individual MBI that is accessible to most LTCF residents while still providing the associated benefits of traditional group MBIs.